Environmental contamination : health risks and ecological restoration - Wong, Ming H. (Boca Raton, Fla. : Taylor & Francis, 2013)
"Drawn from presentations made during the Croucher Advanced Study Institute workshop held in 2010, this volume covers all the fundamentals necessary for contaminated site assessment and remediation. It discusses historical and emerging contaminants, human health, risk assessment and bioremediation. It contains numerous case studies, many of them from the Asia-Pacific region, that look at the effects of rapid industrialization. It also examines both historical and emerging contaminants such as persistent organic pollutants and electronic waste"--
pt. 1. Health impacts and risk assessment -- pt. 2. Emerging chemicals and electronic waste -- pt. 3. Ecological restoration of contaminated sites : bioremediation -- pt. 4. Ecological restoration of contaminated sites : phytoremediation.
From the Croucher Advanced Study Institute workshop 2010, entitled Remediation of contaminated land bioavailability and health risk, held at the Hong Kong Baptist University, between December 9 and 13, 2010.
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Pollution -- Congresses; Restoration ecology -- Congresses; Electronic books